siRNA Mediated Downregulation of RhoA Expression Reduces Oxidative Induced Apoptosis in Retinal Ganglion Cells - Liu, Qian; Liu, Changgeng; Lei, Bo (Current molecular medicine, 2024)
Glaucoma is the second leading cause of blindness. Apoptosis of retinal ganglion cells (RGCs) is an important mechanism of glaucomatous optic injury. Rho kinase expression is significantly increased in apoptotic RGCs. This study aimed to investigate the role of RhoA, a Rho GTPase, on the survival of RGCs and further to explore its potential therapeutic applications. RGCs were treated with siRhoA for 24 hours . Knockdown of RhoA was confirmed with quantitative RT-PCR. Oxidative stress was induced by treating the RGCs with 200 μM of H O for 1 hour, and apoptosis of RGCs was quantified with TUNEL assay , and with flow cytometry. The mRNA expression levels of RhoA, Nogo receptor, caspase 3 and Bcl-2 were evaluated by quantitative RT-PCR, and the protein levels of RhoA, ROCK1, ROCK2, Nogo receptor, caspase 3 and Bcl-2 were evaluated by Western blot. We found siRhoA treatment efficiently downregulated the expression of RhoA in RGCs and protected against H O -induced injury in RGCs . Apoptosis of RGC cells under oxidative stress was quantified in situ using TUNEL assay and confirmed with flow cytometry (FCM). With the knockdown of RhoA, the expression of ROCK1, ROCK2, Nogo Receptor, Casepase-3 were decreased, while the expression of Bcl-2 was increased in both mRNA and protein level. Our data indicated that siRhoA prevented H O -induced apoptosis in RGC cells by modulating the RhoA/ROCK pathway. The results suggested that siRhoA may exert potentially effective neuroprotection for RGCs by reducing injury.